Spotlight on graduate student: Ade Chandra lwansyah, MSc ( industrial chemistry) candidates - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2011)
Ade Chandra lwansyah, 28 years old, was born in Bogor, Indonesia. He received his early education in Bogor and pursued his bachelors degree in Community Nutrition at Bogor Agricultural University (IPB), Indonesia in 2005.